Digital business transformation in current conditions. Part II. - Yu. N. Kafiyatullina; D. A. Kurochkin; D. V. Serdechnyy (Вестник университета)
The growing need for digitalisation of business processes determines the competitiveness of companies in the global and Russian markets. In the current conditions, the importance of reducing physical labor for employees, organizing the working atmosphere and, of course, automating important parts of business processes are the main factors in the life of a modern enterprise. However, the implementation of digital transformation, especially in the current conditions of partial economic isolation, is a complex and ambiguous process. Within the framework of the study, methods for assessing the level of digital maturity of enterprises in the manufacturing sector will be considered. Based on the information provided, recommendations for the digital transformation of business, based on an assessment of the level of readiness for transformation will be formulated.